Therapy with sirolimus in vascular anomalies: the experience of two Italian centers on 14 pediatric patients - Neirotti, A.; Barat, V.; Coppo, P.; La Selva, R.; Manicone, R.; Cotti, R.; Sensini, M.; Mussa, A.; Gatto, M.; Farri, F.; Basso, M. E.; Fagioli, F. (Frontiers in Pediatrics, 2024)
Introduction Vascular anomalies (VAs) constitute a heterogeneous group of tumors and malformations capable of inducing significant clinical events in specific patients, such as the compression of vital organs, pain, functional impairment, or acquired coagulopathy. Molecular investigations into the underlying mechanisms of VAs have unveiled the frequent involvement of the PI3 K/AKT/mTOR pathway. Sirolimus, a specific mTOR inhibitor, has emerged as a potential therapeutic agent; however, its routine clinical application in complex VAs is currently restricted by a lack of extensive clinical experience. Methods Between 2015 and 2024, we administered sirolimus to 14 pediatric patients with various types of vascular anomalies in two Italian centers, subjecting them to clinical and instrumental follow-up to investigate its efficacy and the possible occurrence of adverse events. Results An overall improvement in or stability of their vascular anomalies was reported by 86% of patients. We also assessed toxicity, noting a low prevalence of life-threatening adverse events: only one case of sepsis was reported in a patient with a severe clinical condition, and four cases of recurrent aphthosis (28%) were reported. The most common side effect was dyslipidemia, with 43% of patients developing hypercholesterolemia (21%) or hypertriglyceridemia (21%), although these patients generally did not reach severe levels. Discussion In line with data in the literature, according to our experience, medical therapy with sirolimus should be considered in pediatric patients affected by vascular anomalies.